Determinants of flood fatalities: evidence from a panel data of 79 countries - Padli, Jaharudin; Habibullah, Muzafar Shah; Abdul Hamid, Baharom (Universiti Putra Malaysia Press, 2013)
There is available evidence from different parts of the world that floods and storm account for about 67 percent of the natural disasters. While, earthquake, landslides, drought, extreme temperature, wildfire and volcano eruptions contribute to the remaining 23 percent. In many developing countries, the frequent occurrences of natural disasters, particularly floods are not uncommon. Yearly recurrence of floods bring devastate economies. The objective of the present study is to investigate factors that can mitigate the impact of floods on human fatalities and damages. We use a panel of 79 countries for the period of 1981-2005 and employ the two-step system GMM estimator to show that the level of economic development, population, investment, openness and education impact flood fatalities, total people affected and total cost of damages.